Light‐Driven Awn‐Footed Soft Robots. Issue 8 (18th April 2022) - Song, Xiaodong; Qiu, Xiaxin; Huang, Xiaowen; Xu, Mengda; Zhang, Lidong
Abstract: Anisotropic friction, widely existing on biological surface, is vital for motion or transporting cargoes in nature; however, the challenge remains to introduce anisotropic friction into soft robotic systems. Herein, an assembling method is reported to introduce elastic awns of Setaria viridis to a soft robot, in which the elastic awn with anisotropic surface structures is capable of giving rise to the anisotropic friction. The body of soft robot is composed of three functional layers: polydimethylsiloxane@carbon nanotubes layer that generates photothermal effect, poly(vinylidene difluoride) layer, able to direct the motion of robot, and waxy rice amylopectin@polyvinyl alcohol layer for humidity response. The humidity‐responsive layer improves the shape recoverability of the soft robot during the response to light irradiation, and thus extending its motion lifetime. The elastic‐awn legs support the body of robot and push the robot forward by the positive friction. Based on the anisotropic friction, the controllable motion of various soft robots is successfully achieved in response to external stimuli. Abstract : A soft robot with elastic awn of Setaria viridis as legs is reported. The body of soft robot contains three functional layers: layer of polydimethylsiloxane@carbon nanotubes that generates photothermal effect, poly(vinylidene difluoride) layer, able to direct the motion of robot, and amylopectin@polyvinyl alcohol layer for humidity response. The elastic‐awn legs support the body of robot and can provide positive friction to push the robot forward in response to external stimuli.